Fermi surface of IrTe2 in the valence-bond state as determined by quantum oscillations - Blake, S; Watson, MD; McCollam, A; Kasahara, S; Johnson, R; Narayanan, A; Pascut, G; Haule, K; Kiryukhin, V; Yamashita, T; Watanabe, D; Shibauchi, T; et al. (2014)
We report the observation of the de Haas-van Alphen effect in IrTe2 measured using torque magnetometry at low temperatures down to 0.4 K and in high magnetic fields up to 33T. IrTe2 undergoes a major structural transition around 283 K due to the formation of planes of Ir and Te dimers that cut diagonally through the lattice planes, with its electronic structure predicted to change significantly from a layered system with predominantly three-dimensional character to a tilted quasi-two dimensional Fermi surface. Quantum oscillations provide direct confirmation of this unusual tilted Fermi surface and also reveal very light quasiparticle masses (less than 1 me), with no significant enhancement due to electronic correlations. We find good agreement between the angular dependence of the observed and calculated de Haas-van Alphen frequencies, taking into account the contribution of different structural domains that form while cooling IrTe2.